Homogenization of the Linear and Non-linear Mechanical Behavior of Polycrystals - Jöchen, Katja (KIT Scientific Publishing, 2013)
This work is dedicated to the numerically efficient simulation of the material response of polycrystalline aggregates. Therefore, crystal plasticity is combined with a new non-linear homogenization scheme, which is based on piecewise constant stress polarizations with respect to a homogeneous reference medium and corresponds to a generalization of the Hashin-Shtrikman scheme. This mean field approach accounts for the one- and two-point statistics of the microstructure.
English
Keywords: mean-field approach; homogenization; polycrystalline materials; inelastic properties